Wissensknoten im deutschen Städtesystem. Die Identifizierung von Knoten durch Kombination territorialer und Netzwerkperspektiven - Growe, Anna; H. Blotevogel, Hans (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
This paper identifies hubs of knowledge-based labour in the German urban system from two perspectives: the importance of a metropolitan region as a place and the importance of a metropolitan region as an organisational node. This combination of a network perspective with a territorial perspective enables the identification of hubs. From the functional perspective, hubs are understood as important nodes of national and global networks, established by flows of people, goods, capital and information as well as by organisational and power relations. From the territorial perspective, hubs are understood as spatial clusters of organisations (firms, public authorities, non-governmental organisations). The functional focus of the paper lies on knowledge-based services. Based on data about employment and multi-branch advanced producer service firms, four main types of metropolitan regions are identified: growing knowledge hubs, stagnating knowledge hubs, stagnating knowledge regions and catch-up knowledge regions. The results show an affinity between knowledge-based work and bigger metropolitan regions as well as an east-west divide in the German urban system.
Keywords: Hubs; Space of places; Space of flows; Knowledge economy; Metropolitan regions; Germany